JURNAL PENGARUH KOMITMEN, KEPERCAYAAN DAN KOMUNIKASI TERHADAP LOYALITAS PELANGGAN JASA KURSUS JCC (Jogja Course Center) - Hairul Anam (JURNAL EKOBIS DEWANTARA, 2018)
This study aims to determine the effect of communication, trust, and commitment both partially and simultaneously to the JCC (jogja course center) customers loyalty. This study used a non-probability sampling techniques using purposive sampling. After conducting a literature review and preparing hypotheses, data was collected through a questionnaire method then it was distributed to 100 JCC (jogja course center) customers. The results show the multiple linear regression equation was LP=bKMN+bKP+b3KSI+e. Which means as simultaneously commitment (KMN), trustworthiness (KP), and communication (KSI) make a major contribution to the customers loyalty. Partially, the variables of trust and communication have a significant effect on JCC (jogja course center) customers loyalty. While to the commitment has no significant effect on JCC (jogja course center) customers loyalty. Based on three independent variables that contribute a dominant influence on the loyalty of JCC (jogja course center) customers are trust variables.